Antidiabetic potential of Gynura procumbens (Lour.) Merr.: a review of in vitro and in vivo studies - Mohd Nor, Nurul Hafizah; Jaffar, Farah Hanan Fathihah; Kashim, Mohd Izhar Ariff Mohd; Mokhtar, Mohd Helmy (Frontiers in Pharmacology, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease that affects around 10.5% of adults worldwide. It leads to significant complications, including nephropathy, retinopathy and cardiovascular disease. Conventional treatments for DM often involve the long-term use of pharmacological agents, which can be costly and are associated with various side effects. Due to these challenges, there is growing interest in complementary treatments, particularly those derived from botanical drugs, to explore their potential antidiabetic properties. Gynura procumbens (Lour.) Merr. (GP) has been scientifically studied and shown to possess antioxidant properties that lead to a significant reduction in blood glucose levels and an improvement in lipid profile. The aim of this review is therefore to provide a detailed overview of the current state of knowledge on the antidiabetic potential of GP based on four in vitro studies and 12 in vivo studies. GP extract in concentrations between 50 mg and 3,000 mg shows promising potential as an antidiabetic agent, with some studies suggesting comparable efficacy to metformin in the treatment of diabetes. In addition, phytochemical studies of GP have revealed a diverse phytochemical metabolite, with a predominance of polyphenolic metabolites, especially phenolic acids and flavonoids, extracted from various solvents. However, the evidence remains mixed, as other studies have presented varying results on the efficacy of GP in the treatment of diabetes. This could be due to the lack of standardisation of the extract preparation, insufficient information on the bioactive metabolite responsible for the observed effects and the lack of clinical studies. Therefore, more comprehensive studies including clinical trials are needed to clarify the discrepancies in the findings and provide a clearer effect of GP in alleviating DM. With these improvements, GP could complement standard DM treatments and offer patients a safer, more holistic approach.